The end or the return of Sovietology? – Reflections on the fall of the Berlin Wall and beyond - Fryer, Paul (International Journal of Contemporary Economics and Administrative Sciences, 2016)
Introduction for the journal and reflections of the academic challenges for scholars of Sovietology, Russian and Border studies since the fall of the Berlin Wall.